1982
DOI: 10.1139/m82-110
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of plant pathogenic fungi by Trichoderma harzianum

Abstract: Trichoderma harzianum excreted β-1, 3-glucanase and chitinase into the medium when grown on laminarin and chitin, respectively, or on cell walls of the pathogen Sclerotium rolfsii, as sole carbon source. Trichoderma harzianum also showed high activity of both enzymes when grown on homogenized S. rolfsii sclerotia. Glucanase activity increased by 67% when the fungus was grown on a mixture of laminarin and glucose (3:1, v/v). Similarly, high lytic activity was detected in wheat bran culture of the fungus and in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
195
0
11

Year Published

1996
1996
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 441 publications
(218 citation statements)
references
References 16 publications
12
195
0
11
Order By: Relevance
“…Extracellular secretion of variable enzymes profiles between biocontrol strains of T. harzianum have been observed in response to polysaccharides and host cell walls (Elad et al 1982, Mach et al 1999. This study found interspecies variation in expression of three mycoparasitismrelated genes.…”
Section: Discussionmentioning
confidence: 99%
“…Extracellular secretion of variable enzymes profiles between biocontrol strains of T. harzianum have been observed in response to polysaccharides and host cell walls (Elad et al 1982, Mach et al 1999. This study found interspecies variation in expression of three mycoparasitismrelated genes.…”
Section: Discussionmentioning
confidence: 99%
“…Samples were brought to laboratory and stored at 4°C until used. Five-fold serial dilutions of each soil samples were prepared in sterilized distilled water and 0.5 ml diluted sample was poured on the surface of Trichoderma Specific Medium (TSM) [8]. Plates were incubated at 28 ± 2°C for 96 h. Morphologically different colonies appearing on the plates were purified in the Potato Dextrose Agar (PDA) (HiMedia, India).…”
Section: Soil Samples and Isolationmentioning
confidence: 99%
“…Thèse fungi produce extracellular cell-wall degrading enzymes, including chitinases, cellulases, /3-1,3-glucanases and proteases. The mycolytic activity of thèse enzymes has long been recognized as a major factor in the hyperparasitic mechanism exerted by Trichoderma (Elad et al, 1982). Différent stratégies hâve been tried to increase the chitinase activity of one of the most potent biocontrol species, T. harzianum.…”
Section: Aims and Methods Of Strain Improvementmentioning
confidence: 99%